Use the four-step process to find \( f^{\prime}(x) \) and then find \( f^{\prime}(-2), f^{\prime}(3) \), and \( f^{\prime}(7) \). \( f(x)=2 x^{2}+x-1 \) \( f^{\prime}(x)=\square \) \( f^{\prime}(-2)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(3)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(7)=\square \) (Type an integer or a simplified fraction.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \( f^{\prime}(x) \) using the four-step process, we first compute the derivative of \( f(x) = 2x^2 + x - 1 \). 1. **Identify the function**: We have \( f(x) = 2x^2 + x - 1 \). 2. **Apply the power rule**: The derivative of \( x^n \) is \( n x^{n-1} \). Thus: - For \( 2x^2 \), the derivative is \( 2 \cdot 2x^{2-1} = 4x \). - For \( x \), the derivative is \( 1 \). - For \( -1 \), the derivative is \( 0 \). 3. **Combine the results**: Adding these derivatives together, we get: \[ f^{\prime}(x) = 4x + 1. \] 4. **Simplify**: This is already simplified as \( 4x + 1 \). Now, let's find the specific values: 1. **Calculate \( f^{\prime}(-2) \)**: \[ f^{\prime}(-2) = 4(-2) + 1 = -8 + 1 = -7. \] 2. **Calculate \( f^{\prime}(3) \)**: \[ f^{\prime}(3) = 4(3) + 1 = 12 + 1 = 13. \] 3. **Calculate \( f^{\prime}(7) \)**: \[ f^{\prime}(7) = 4(7) + 1 = 28 + 1 = 29. \] Putting everything together, we have: \[ f^{\prime}(x) = 4x + 1 \] \[ f^{\prime}(-2) = -7 \] \[ f^{\prime}(3) = 13 \] \[ f^{\prime}(7) = 29 \]